(untitled) (International Journal of Environmental Sciences, 2025)
This paper explores the importance of environmental performance indicators (EPIs) in the effective governance of smart cities. It seeks to suggest and create a framework of EPIs which can aid in sustainable urban development, enhance decision-making, and facilitate performance evaluation in technologically advanced urban ecosystems. This approach systematically describes a smart city analytics framework composed of the hypothetical optimal smart city structure. It describes a systematic strategy for indicator selection based on data, availability, measurability, relevance to policy goals in the context of smart cities. Urban environmental management and control, benchmarking, and comparative analysis, and policy change are enhanced through the refined EPIs within the urban smart city infrastructure. This research underscores the data governance paradigm in the realization of urban sustainability.